Distribution Patterns of Pneumonia in Yogyakarta Province, Indonesia: A Descriptive Analysis for 2013-2022 - Nisa Zanuarto; Riflan Saputra; Mutiara Islami; Putri Revina; Ratna Sari (Journal of Health Science and Pharmacy, 2026)
Background: Pneumonia is an acute respiratory infectious disease that continues to pose a significant public health challenge, particularly in developing countries such as Indonesia. It remains one of the leading causes of morbidity and mortality, especially among vulnerable age groups, including children under five and the elderly. In the Special Region of Yogyakarta (DIY) province, pneumonia persists as a major health issue. Objectives: This study aims to analyze the distribution patterns of pneumonia in Yogyakarta Province by examining temporal trends, geographic distribution, and demographic characteristics from 2013 to 2022. Methods: A quantitative descriptive approach was employed in this study, utilizing secondary data from the DIY Province Health Profile. The data were analyzed both tabulatively and visually, using trend charts and distribution maps to depict the distribution by year, district/city, age, and gender. Results: The analysis revealed fluctuations in the number of pneumonia cases from 2013 to 2022, with significant peaks observed in 2015 and 2019. Spatially, Sleman and Bantul districts recorded the highest number of cases. Demographically, the highest incidence rates were observed in the under-five (0-5 years) and elderly (>60 years) age groups. Gender distribution showed a slightly higher incidence in males compared to females. Conclusion: The distribution of pneumonia in Yogyakarta Province is uneven, with cases being concentrated in densely populated areas and among vulnerable age groups. These findings highlight the need for targeted, region-specific, and age-based intervention strategies to effectively prevent and control pneumonia. Keywords: Pneumonia, spatial distribution, Yogyakarta, descriptive analysis